صورة الإنسان المسؤول (الحاكم) في خطب نهج البلاغة (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2016)
يدرس البحث صورة الإنسان المسؤول في خطب نهج البلاغة , فيبدأ بعرض آراء بعض الفلاسفة وعلماء الاجتماع في الحاكم المسؤول , وتقديمهم جملة من العوامل المؤثّرة في سلوكه , وتوضيح بعض الظروف التي تجعل منه مسؤولاً . يركّز البحث على الإنسان المسؤولوالواجبات الملقاة على عاتقه إزاء نفسه ورعيّته ومسؤولياته أمام الله تعالى .كما يقدّم البحث دراسةً فنيّةً جماليّةًلأنموذجٍمن نماذج خطب النهج التي تتحدّث عن مسؤوليات الحاكم , فيُظهر البحث الجوانب الجماليّة فيها وأثر الصور الفنيّة واللغة والإيقاع الموسيقيّ في جلاء صورة المسؤول وتذكيره بواجباته . The Research examines the image of man in charge in the Speeches of Nahj ulBalaghah. It starts with presenting the views of some philosophers and sociologists about man in charge (the ruler), introducing number of factors affecting his behavior. In addition, it clarifies some of the circumstances that make him responsible. The Research, also, focuses on the man in charge with duties entrusted to him regarding himself, his flock and his responsibilities before God. It also offers an artistic and aesthetic study of one of the Speeches models that talks about the responsibilities of the ruler. The Research shows the aesthetic aspects and the impact of art images, language, rhythm on showing the official image of man in charge and reminding him of his duties.